MODERN TRENDS OF DEVELOPMENT OF INTERNATIONAL DERIVATIVES MARKET - V. Shelydko; V. Virchenko (Вісник Київського національного університету імені Тараса Шевченка. Серія Економіка)
Article is devoted to analysis of structure and peculiarities of development of the international derivatives market. The history of formation of the international derivatives market is investigated. The nature, functions and advantages of use of derivatives, and also their role in the modern international securities market are defined. Classification of financial derivatives is considered. Product lines of financial derivatives are analyzed. The regional structure of the international derivatives market and dynamics of its development are investigated. The comparative characteristic of volumes and structure of exchange and over-the-counter segments of international derivatives market are carried out. Dynamics and structure of international markets of interest-bearing derivatives and currency derivatives are analyzed. The fundamental trends of development of the modern international derivatives market are defined.